The Relationship between Body Mass Index and Lung Vital Capacity - Batubara, Frisca Ronauli; Marantuan, Randolph Serep; Pongsammin, Francisco (Jurnal KESANS : Kesehatan dan Sains, 2025)
Vital Capacity (VC) serves as one of the main parameters in assessing lung function. Obesity, which can be measured using Body Mass Index (BMI) and waist circumference, has the potential to affect respiratory mechanics and decrease lung function. Medical students with limited physical activity are at risk of experiencing reduced VC due to increased BMI and central obesity. This study aims to determine the relationship between BMI and waist circumference with VC among 2023 cohort students of the Faculty of Medicine, Universitas Kristen Indonesia. This research is an observational study with a cross-sectional design. A total of 57 students participated as samples. Data were collected through measurements of BMI, waist circumference, and VC using spirometry. Chi-square test was used for analysis. Results showed that 54.4% of respondents had abnormal BMI, 40.4% had central obesity, and 57.9% exhibited abnormal vital capacity. A significant relationship was found between BMI and VC (p=0.001), as well as between waist circumference and VC (p=0.010). These findings indicate that increased BMI and waist circumference may contribute to reduced lung function.